Analysis of Design Features of Fish Trawls and Shrimp Trawls of Thoothukkudi Coast - N., Neethiselvan; G., Brucelee (Fishery Technology, 2025)
The investigation deals with the comparison of body proportions of fish trawls and coastal shrimp trawls of Thoothukkudi coast with each other and with those of a standard FAO fish cum shrimp trawl. Significant variations could be noticed between fish trawls and coastal shrimp trawls of Thoothukkudi coast with respect to parameters viz. length of bottom wing, breadth of top bosum, breadth of bottom bosum, breadth and length of second belly as evidenced from low percentages of overlapping (